Drought-resistant of nectarine varieties and forms (Prunus persica (L.) Batsch subsp. nectarina (Ait.) Shof.) with the sign of male infertility. - О. О. Іващенко; Є. П. Шоферістов; Ю. В. Іващенко; Р. А. Пилькевич (Plant Varieties Studying and Protection)
The drought-resistance of 15 nectarine varieties and forms with a sign of male infertility is studied. The research identified genotypes with varying degrees of drought-resistance. The greatest degree of drought-resistance demonstrated the form 33-3-1, 512-86,41-15-2, and grade Kul'dzhinskiy 4x, Krymtsuht, Elbertaziya.